Essays on civil conflict, political regimes, and natural endowments - Gupta, Satyendra Kumar (2017)
History is important in understanding cultural traits and the quality of institutions across countries. Transformation to sedentary agricultural practices was a key historic event in human history. Gradually, agriculture became an important activity for sedentary societies, and consequently, land productivity became the most important resource for agriculture in the societies. This study measures land productivity by potential crop yield. The potential crop yield index is constructed using crop yield (measured in tons per hectare per year) from the Global Agro-Ecological Zones (GAEZ) project from the Food and Agriculture Organization (FAO) and the caloric content of various crops from the US Department of Agriculture Nutrient Database for Standard Reference (source: Galor and Özak (2016)). In the first chapter, I hypothesize that as societies started fighting over control of the most productive land, a culture of violence and conflict developed. The empirical results establish that the emergence and persistence of intrastate conflict incidence since 1960 were influenced by regional agro-ecological factors captured by the extent of variation in crop yield potential. Our results, based on cross-country and grid-level analysis, indicate that higher potential crop yield variability within a country that is exogenous to both human intervention and regional culture increases the likelihood of intrastate conflict. Our findings are strengthened by the inclusion of various geographical, institutional, and potentially confounding economic development correlates. In the second chapter, I focus on colonization by the Western European powers after the discovery of the New World. I hypothesize that the timing and duration of colonization was strongly influenced by regional land productivity. In particular, an area’s potential average crop yield is shown to have an significant and influential effect on the timing and duration of colonization, where more fertile areas tended to be colonized earlier and had a longer period of colonization. The results are consistent with historical evidence such as the quest for new territories in order to produce sugar, tea, timber, and other commodities. These efforts supported industrial growth in Europe, which provided its population with the calories needed. My findings are bolstered by the inclusion of other indicators of early development, as well as the geographical and ecological conditions that were important for European settlement in the colonized territories. My hypothesis is also supported by a grid-cell level analysis, which mitigates any endogeneity concern in the cross-country analysis. In the third chapter, I argue that an optimal level of potential crop yield is inductive of a democratic political regime. Empirical results establish a humped shaped association between crop yield and the extent of democracy in a cross-country analysis. These findings are supported by the inclusion of other possible confounders such as: the quality of institutions, indicators of early development, and various other determinants of democracy identified in extant literature. The hypothesis is also supported by sub-national and pre-colonial societies’ datasets. The next three chapters identify and empirically establish the role of land productivity in the emergence of culture of conflict, the occurrence of important historic events, and the development of modern institutions. The last chapter of this Ph.D. dissertation draws the necessary conclusions.